MENGEMBANGKAN PERILAKU SEHAT MELALUI PENDEKATAN SOCIAL LEARNING THEORY - Fatimah Saguni (Hunafa: Jurnal Studia Islamika, 2007)
Prior to 1990s, the major cause of death is a cute disorder such as tuberculosis, small fox, leprosy and various infections convinced to be brought about by viruses and bacteria. Therefore, to cure them, the procedure used is more oriented to the use of medicines. It is true that by using medicine, those kinds of diseases can be minimized. However, in later decades, some diseases such as skin cancer, diarrhea and vomiting are convinced by experts as being caused not only by viruses and bacteria but also by behavioral forms of an individual himself. This article discusses the effort to develop healthy behaviors through a social learning theory approach.   Kata Kunci: Perilaku sehat, social learning theory